The test on the inhomogeneous strain field and creep rupture behavior of the weld joint at elevated temperature by digital image correlation method. (February 2021) - Song, Ming; Sun, Chao; Zhang, Xuetao; Yu, Haiyang; Sun, Yonghui; Liu, Kai; Xu, Tong
Highlights: With oxidation-resistant coatings, stable speckles was produced at ~ 700 ℃ for DIC test. The long-term strain distribution of the weld joint was in-situ tested at ~ 700 ℃ by DIC. All three creep stages and MCR of every local zone in weld joint had been obtained simultaneously. Abstract: The digital image correlation (DIC) method was applied for monitoring the short and long term inhomogeneous deformation and rupture behavior of the weld joint at elevated temperature. In order to prevent the surface oxidation of the metal during the long time exposure at elevated temperature and offer a series of stable surface patterns for the DIC sensing, the thin metallic coating was introduced. Then the strain field and rupture of the weld joint were tested successfully not only during the short term tensile test but also the long term creep test. The results showed a good performance on distinguishing the deformation differences at local zone of the weld joint. Especially, the three-stage creep behavior of the local zones could be measured simultaneously, even though the weakest zone controlling the creep rupture, which is helpful to study the creep rupture behavior of the weld joint and develop the creep life evaluation method or the creep failure monitoring technology. Also the limitations of this method were discussed briefly.